Circulating T helper and T regulatory subsets in untreated early rheumatoid arthritis and healthy control subjects - Pandya, Jayesh M.; Lundell, Anna‐Carin; Hallström, Magnus; Andersson, Kerstin; Nordström, Inger; Rudin, Anna (Journal of leukocyte biology, 2016)
Blood T helper profile separates ueRA patients from controls by a skewed balance toward a CCR4+CXCR3− Th2 and Th17 phenotype in patients. The pathogenic role and frequency of T cell subtypes in early rheumatoid arthritis are still unclear. We therefore performed a comprehensive analysis of the circulating T cell subtype pattern in patients with untreated early rheumatoid arthritis compared to healthy control subjects. Peripheral blood mononuclear cells were obtained from 26 patients with untreated early rheumatoid arthritis and from with 18 age‐ and sex‐matched healthy control subjects. T helper cell types Th0, Th1, Th2, Th17, and Th1/17 and nonclassic T helper subsets were defined by flow cytometry based on the expression of chemokine receptors CCR4, CCR6, and CXCR3. Regulatory T cells were defined by expression of CD25+ CD127low and also FOXP3. CXCR5+ cells among regulatory and nonregulatory T cells were defined as T follicular regulatory and T follicular helper cells, respectively. The phenotype of T cell subsets was confirmed by transcription factor and cytokine secretion analyses. Multivariate discriminant analysis showed that patients with untreated early rheumatoid arthritis were segregated from healthy control subjects based on the circulating T cell subset profile. Among the discriminator subsets, CCR4+CXCR3− (Th2 and Th17), CTLA4+ and FOXP3+ subsets were present in significantly higher frequencies, whereas CCR4− (Th1/Th17, CCR6+CCR4−CXCR3−, and Th1) subsets were present in lower frequencies in patients with untreated early rheumatoid arthritis compared with healthy control subjects. The proportions of Th2 and Th17 subsets associated positively with each other and negatively with the CXCR3+/interferon γ‐secreting subsets (Th1 and Th1/Th17) in patients with untreated rheumatoid arthritis. The proportions of Th2 cells increased with age in patients with untreated early rheumatoid arthritis and healthy control subjects. The dominance of circulating CCR4+CXCR3– T helper subsets (Th2 and Th17) in untreated early rheumatoid arthritis point toward a pathogenic role of these cells in early stages of the disease.